Relationship Between Verbal Fluency Performance, Fight Exposure, and Subcortical Region Brain Volumes in Professional Fighters. (26th July 2019) - Bennett, L; Bernick, C; Banks, S
Abstract: Purpose: Verbal fluency performance has been shown to be sensitive to preclinical cognitive changes in neurodegenerative diseases and may detect early, trauma-related cognitive and volumetric changes amongst professional fighters. Baseline verbal fluency performance and volumes of relevant subcortical brain structures were expected to decline as number of professional fights (NoPF) increased, while controlling for education. Methods: Baseline letter and semantic fluency performance, NoPF, and structural brain imaging from 548 active and retired fighters who participated in the Professional Fighters Brain Health Study were considered. ANCOVAs were conducted to assess differences in verbal fluency performance by NOPF, while controlling for years of education. Number of professional fights were stratified into low (0-20 fights), medium (21-40 fights), and high (41 or more fights). Results: Semantic fluency performance differed across the three levels of NoPF (F(2, 542)=4.56; p<.02). In addition, significant positive correlations between semantic fluency performance and volumes in the following regions were observed: left thalamus, left putamen, left pallidum, bilateral caudates, bilateral amygdalae, bilateral hippocampi, and bilateral accumbens (all p's<.05). In contrast, letter fluency performance was not significantly associated with NoPF or volumes of relevant subcortical brain structures (all p's>.05). Conclusion: Semantic fluency may be low-cost, easy-to-administer harbinger of emerging cognitive dysfunction and lower volumes in related subcortical brain regions. Additional assessment of clinical utility is necessary.